Accelerated Evolution of Schistosome Genes Coding for Proteins Located at the Host–Parasite Interface - Philippsen, Gisele S. (Genome Biol Evol, 2015)
Study of proteins located at the host–parasite interface in schistosomes might provide clues about the mechanisms utilized by the parasite to escape the host immune system attack. Micro-exon gene (MEG) protein products and venom allergen-like (VAL) proteins have been shown to be present in schistosome secretions or associated with glands, which led to the hypothesis that they are important components in the molecular interaction of the parasite with the host. Phylogenetic and structural analysis of genes and their transcripts in these two classes shows that recent species-specific expansion of gene number for these families occurred separately in three different species of schistosomes. Enrichment of transposable elements in MEG and VAL genes in Schistosoma mansoni provides a credible mechanism for preferential expansion of gene numbers for these families. Analysis of the ratio between synonymous and nonsynonymous substitution rates (dN/dS) in the comparison between schistosome orthologs for the two classes of genes reveals significantly higher values when compared with a set of a control genes coding for secreted proteins, and for proteins previously localized in the tegument. Additional analyses of paralog genes indicate that exposure of the protein to the definitive host immune system is a determining factor leading to the higher than usual dN/dS values in those genes. The observation that two genes encoding S. mansoni vaccine candidate proteins, known to be exposed at the parasite surface, also display similar evolutionary dynamics suggests a broad response of the parasite to evolutionary pressure imposed by the definitive host immune system.